Evaluating the BBAQ Program as a Strategy for Enhancing Quranic Education Quality: A CIPP Model Analysis - Muhammad Firdaus; Siti Julaiha (Journal of Educational Management Research, 2025)
This study aims to evaluate the Bina Baca Al-Qur'an (BBAQ) program at school as an effort to improve the quality of Quranic education in elementary schools. The research focuses on analyzing the program's foundation, resource readiness, activity mechanisms, and student outcomes. The study's objects include Quranic teachers, control books, memorization targets per grade level, and the implementation of reading and memorization activities held Monday through Thursday. The study uses the CIPP evaluation model, which assesses the context, input, process, and product through document review and activity observation. The results indicate that the BBAQ program aligns with the school's needs, effectively addressing the variation in students' reading abilities and supporting the school's religious vision. Regarding input, the school has provided adequate supporting components; however, teacher competence and documentation consistency need improvement. The implementation process is routine but inconsistent due to teacher rotation, time constraints, and varying student abilities. In terms of product, the program shows strong memorization outcomes, with many students completing Juz 30, while reading achievements remain uneven due to the lack of clear achievement standards per grade level.